2013
DOI: 10.1039/c3an00956d
|View full text |Cite
|
Sign up to set email alerts
|

A photoelectrochemical immunosensor for tris(2,3-dibromopropyl) isocyanurate detection with a multiple hybrid CdTe/Au–TiO2 nanotube arrays

Abstract: In this paper, tris(2,3-dibromopropyl) isocyanurate (TBC) is for the first time as far as we know determined by ultrasensitive photoelectrochemical (PEC) immunoassay using an antibody-modified ternary hybrid CdTe/Au-TiO2 nanotube arrays (NTAs) photoelectrode, developed by the pulse electrodeposition technique. The as-prepared hybrid shows enhanced photon absorption and photocurrent response, which subsequently increased the photoelectrical conversion efficiency in the visible region. TBC-antibody (Ab) was deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…The agglomerated nanocrystallites result in decreased photocurrent and hence are less effective as a sensitizer. Similar results have been reported by Gao et al 50 and Feng et al 51 in the case of CdTe-modied TiO 2 nanotube arrays. Therefore, further studies were limited to 3, 5 and 7 cycles of deposition.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The agglomerated nanocrystallites result in decreased photocurrent and hence are less effective as a sensitizer. Similar results have been reported by Gao et al 50 and Feng et al 51 in the case of CdTe-modied TiO 2 nanotube arrays. Therefore, further studies were limited to 3, 5 and 7 cycles of deposition.…”
Section: Resultssupporting
confidence: 90%
“…The photoelectrochemical responses obtained in our study are higher than the values reported previously for various sensitized-TiO 2 photoelectrodes. 4,5,7,15,51,60,56,63 Also, the results obtained in this study are in agreement with results reported by Yang et al 44 The electronic properties of sensitized and unsensitized TiO 2 NTA lms were determined using the Mott-Schottky (MS) method. The measurements were performed at a frequency of 100 Hz, with the potential scan range from 0.5 to À1 V (vs. SCE) under illumination.…”
Section: Photoelectrochemical Measurementssupporting
confidence: 91%
“…These aggregated Mn x Cd y Se nanocrystals in turn act as recombination centers for photoinduced electron-hole pairs, rendering them less effective as sensitizers. [41][42][43] Moreover, increased loading leads to the blockage of nanotubes pores resulting into a poor electrolyte penetration. Thus, a variation in the number of deposition cycles was found to have a profound effect on the current density.…”
Section: Resultsmentioning
confidence: 99%
“…Several methods to detect TBC in environment were established including gas chromatography (GC) and liquid chromatography coupled with mass spectrometry (LC-MS) [2]. Zhao [3] and Feng [4] et al developed electrochemiluminescence (ECL) and photoelectrochemical immunosensor (PCI) techniques on the basis of a series of inorganic nanoparticles with good sensiticity and low detect limit. However, these protocols are either much complicated, or need relatively expensive equipments.…”
Section: Introductionmentioning
confidence: 99%